Ginekološka onkologija (University of Maribor Press, 2020)
Gynecologic Oncology. The textbook of Gynecologic Oncology is the first textbook in Slovenia to comprehensively address gynecologic cancers in four groups of chapters: Basic Science in Gynecologic Oncology, Examination Methods in Gynecologic Oncology, Treatment of Malignant Gynecologic Tumors, and Malignant Gynecologic Tumors by Location. The chapters provide descriptions of etiologic and epidemiological factors of gynecologic malignancies, clinical and pathological characteristics, clinical picture, diagnostic and treatment procedures, and the rehabilitation of gynecological oncological patients. A total of 104 chapters have been contributed by 72 experts in various fields of medicine treating gynecological malignancies on a daily basis. The textbook is the joint work of three leading institutions in Slovenia that treat female cancer patients: the Ljubljana Institute of Oncology, the Gynecology Division of the University Medical Center Ljubljana and the Division of Gynecology and Perinatology of the University Medical Center Maribor. The textbook is intended for a wide range of readers interested in the rapidly evolving field of gynecologic cancer treatment.